The foundations of laissez-faire : the economics of Pierre de Boisguilbert - Faccarello, Gilbert (Routledge studies in the history of economics., 2001)
This is the first full length study of Boisguilbert's work to appear in English. It contains an extended discussion of the context in which Boisguilbert worked, as well as a detailed analysis of his life and work.